Differences in clinical characteristics and outcome of de novo heart failure compared to acutely decompensated chronic heart failure – systematic review and meta-analysis. Issue 4 (4th July 2021) - Pranata, Raymond; Tondas, Alexander Edo; Yonas, Emir; Vania, Rachel; Yamin, Muhammad; Chandra, Alvin; Siswanto, Bambang Budi
Abstract: Background: Recent evidence showed that the characteristics and outcome of those with de novo heart failure (HF) and acutely decompensated chronic heart failure (ADCHF) were different. We aimed to perform a comprehensive search on the clinical characteristics and outcome of patients with de novo HF and ADCHF. Methods: We performed a comprehensive search on de novo/new onset acute HF vs ADCHF from inception up until December 2019. Results: There were 38320 patients from 15 studies. De novo HF were younger and, had less prevalent hypertension, diabetes mellitus, ischaemic heart disease, chronic obstructive pulmonary disease, atrial fibrillation, and history of stroke/transient ischaemic attack compared to ADCHF. Five studies showed a lower NT-proBNP in de novo HF patients, while one study showed no difference. Valvular heart disease as aetiology of heart failure was less frequent in de novo HF, and upon sensitivity analysis, hypertensive heart disease was more frequent in de novo HF. As for precipitating factors, ACS (OR 2.42; I 2 :89%) was more frequently seen in de novo HF, whereas infection was less frequently (OR 0.69; I 2 :32%) in ADCHF. De novo HF was associated with a significantly lower 3-month mortality (OR 0.63; I 2 :91%) and 1-year (OR 0.59; I 2 :59%) mortality. Meta-regression showed that 1-year mortality did not significantly vary with age ( p  = .106), baseline ejection fraction ( p  = .703), or HF reduced ejection fraction ( p  = .262). Conclusion: Risk factors, aetiology, and precipitating factors of HF in de novo and ADCHF differ. De novo HF also had lower 1-year mortality and 3-month mortality compared to ADCHF.